2011
DOI: 10.1111/j.1600-0838.2010.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Late specialization: the key to success in centimeters, grams, or seconds (cgs) sports

Abstract: A controversial question within elite sports is whether young athletes need to specialize early, as suggested by Ericsson et al., or if it is more beneficial to follow the path of early diversification proposed by Côté et al., which includes sampling different sport experiences during childhood and specializing later on during adolescence. Based on a Danish sample of 148 elite and 95 near-elite athletes from cgs sports (sports measured in centimeters, grams, or seconds), the present study investigates group di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0
20

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(228 citation statements)
references
References 18 publications
6
190
0
20
Order By: Relevance
“…Inter-estingly, an editorial by Ericsson ( 18) highlights how his earlier work has actually been misconstrued in recent times, citing that expert performance does not simply require the accumulation of 10,000 hours of deliberate practice and that the focus should not be placed on simply accruing a set number of hours in any given activity. Furthermore, re-searchers have shown that late specialization and reduced levels of specific training during childhood are significant predictors of elite performance in adulthood ( 36). Research-ers have also shown that youth who participate in a greater breadth of sports at a younger age performed better in gross motor coordination tasks and had a reduced injury risk in comparison with children who specialized in a single sport at an early age (22,24).…”
Section: Athletic Development Modelsmentioning
confidence: 99%
“…Inter-estingly, an editorial by Ericsson ( 18) highlights how his earlier work has actually been misconstrued in recent times, citing that expert performance does not simply require the accumulation of 10,000 hours of deliberate practice and that the focus should not be placed on simply accruing a set number of hours in any given activity. Furthermore, re-searchers have shown that late specialization and reduced levels of specific training during childhood are significant predictors of elite performance in adulthood ( 36). Research-ers have also shown that youth who participate in a greater breadth of sports at a younger age performed better in gross motor coordination tasks and had a reduced injury risk in comparison with children who specialized in a single sport at an early age (22,24).…”
Section: Athletic Development Modelsmentioning
confidence: 99%
“…Given current evidence on late specialization (35), variety in young players training should be encouraged. Conversely, careful planning of the design of training programs requires greater innovation and monitoring to be incorporated into busy schedules without risking overload.…”
Section: Considerations For Planning and Deliverymentioning
confidence: 99%
“…Although soccer may be the primary sport that the child participates in, they are likely to develop perceptual and decision-making skills such as visual scanning, anticipation, and movement pattern recognition from participating in similar invasion-based sports (e.g., basketball or rugby). Researchers have also shown that a diversification approach to sampling many different sports during childhood is optimal for the development of gross motor coordination (38) and subsequent athletic performance later in life (56,76). Such research refutes the misnomer of the "10,000-hour rule," which is underpinned by an individual seeking to acquire expertise in a given activity needs to engage in 10,000 hours (or 10 years) of deliberate practice, a theory that has been adopted by previous athletic development models (8).…”
Section: Problem 3: Early Sport Specializationmentioning
confidence: 99%